Effects of physical exercise interventions on balance, postural stability and general mobility in Parkinson’s disease: a network meta-analysis - Patricia Lorenzo-García; Iván Cavero-Redondo; Sergio Núñez de Arenas-Arroyo; María José Guzmán-Pavón; Susana Priego-Jiménez; Celia Álvarez-Bueno (Journal of Rehabilitation Medicine, 2024)
Objective: To assess which type of physical exercise intervention has the most beneficial effects on balance, postural stability and general mobility in patients with Parkinson’s disease. These parameters were assessed using the Activities-specific Balance Confidence (ABC) scale, Berg Balance Scale (BBS), Mini-Balance Evaluation Systems Test (MiniBESTest) and Timed Up and Go Test (TUG).